Building Portals with the Java Portlet API - Linwood, Jeff (Apress, 2012)
IT SHOULD BE possible to build a portal by plugging components from different vendors into a portal from any vendor. These components are portlets, and we explain how to build them in this book. The noble aim of the portlet specification—which arose from Sun’s Java Community Process with the collaboration of Sun, IBM, BEA, and others—was to simplify the process of tying applications into a portal by allowing them to cooperate. That so many vendors have come together to standardize their existing proprietary solutions bodes well for the future of this technology. We believe that portlets and the portlet API will become at least as important to Java application developers as the servlet API has been because portlets make building a truly integrated system that much easier. Any new portal development projects should select a portal that supports the portlet API because independent software vendors now need to write portlets for only one API, not a dozen. Both of us enjoy working with new technology, and there are a lot of new standards for portals, content management systems, business rules, and web services. We hope that you will enjoy learning about portal development as much as we enjoyed writing this book!